Focal partial salvage low-dose-rate brachytherapy for local recurrent prostate cancer after permanent prostate brachytherapy with a review of the literature - Kunogi, Hiroaki; Wakumoto, Yoshiaki; Yamaguchi, Nanae; Horie, Shigeo; Sasai, Keisuke (Journal of Contemporary Brachytherapy, 2016)
Purpose : To investigate the treatment results for focal partial salvage re-implantation against local recurrence after permanent prostate brachytherapy. Material and methods : Between January 2010 and September 2015, 12 patients were treated with focal partial salvage re-implantation for local recurrence after low-dose-rate brachytherapy using 125I seeds. The focal clinical target volume (F-CTV) was delineated on positive biopsy areas in a mapping biopsy, combining the cold spots on the post-implant dosimetry for initial brachytherapy. The F-CTV was expanded by 3 mm to create the planning target volume (PTV) as a margin to compensate for uncertainties in image registration and treatment delivery. The prescribed dose to the PTV was 145 Gy. The characteristics and biochemical disease-free survival (BdFS) rates were analyzed. Genitourinary (GU) and gastrointestinal (GI) toxicities were evaluated using the Common Terminology Criteria for Adverse Events version 4. Results : The median prostate-specific antigen (PSA) level at re-implantation was 4.09 ng/ml (range: 2.91-8.24 ng/ml). The median follow-up time was 56 months (range: 6-74 months). The median RD2cc and UD10 were 63 Gy and 159 Gy, respectively. The 4-year BdFS rate was 78%, which included non-responders. Biochemical recurrence occurred in two patients after 7 and 31 months, respectively. The former was treated with hormonal therapy after biochemical failure, and the latter underwent watchful waiting (PSA at the last follow-up of 53 months: 7.3 ng/ml) at the patient’s request. No patients had grade 3 GU/GI toxicities or died after salvage re-implantation. Conclusions : The partial salvage low-dose-rate brachytherapy used to treat local recurrence after permanent prostate brachytherapy is well-tolerated, with high biochemical response rates. This treatment can be not only a method to delay chemical castration but also a curative treatment option in cases of local recurrence of prostate carcinoma after seed implantation.